An integrative transcriptome analysis reveals a functional role for thyroid transcription factor‐1 in small cell lung cancer. Issue 2 (13th August 2018) - Horie, Masafumi; Miyashita, Naoya; Mattsson, Johanna Sofia Margareta; Mikami, Yu; Sandelin, Martin; Brunnström, Hans; Micke, Patrick; Nagase, Takahide; Saito, Akira
Abstract: Small cell lung cancer (SCLC) is a neuroendocrine tumour that exhibits rapid growth and metastatic spread. Although SCLC represents a prototypically undifferentiated cancer type, thyroid transcription factor‐1 (TTF‐1, gene symbol NKX2‐1 ), a master regulator for pulmonary epithelial cell differentiation and lung morphogenesis, is strongly upregulated in this aggressive cancer type. The aim of this study was to evaluate a functional role for TTF‐1 in SCLC. We demonstrated that achaete‐scute complex homolog 1 (ASCL1), an essential transcription factor for neuroendocrine differentiation, positively regulated TTF‐1 in SCLC cell lines. Subsequently, we described genes and microRNAs (miRNAs) that were possibly controlled by TTF‐1 and identified nuclear factor IB (NFIB), a recently characterised driver of SCLC progression, as a transcriptional target of TTF‐1. Our findings shine light on a regulatory axis in SCLC consisting of ASCL1/TTF‐1/NFIB that potentially contributes to the tumourigenesis of SCLC. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.